SUPPLY FRESHWATER FOR FISHING ON A FISHING VESSEL IN THE SIBOLGA ARCHIPELAGO PORT OF TIBULATI DISTRICT, TAPANULI CENTRAL PROVINCE, NORTH SUMATERA PROVINCE - Febriyanti Sitorus; Polaris Nasution; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractFresh water is an important supply to meet the needs of fishing vessels at sea and to serve the cleanliness needs of fishing ports. Freshwater supplies services will run well if the service runs in accordance with applicable regulations. This study aims to determine the predicted demand, availability and demand of fresh water on fishing vessels and find out how the application of Standard Operating Procedures (SOP) and Quality of Freshwater Supplies Services in PPN Sibolga. To find out things related to the research objectives, interviews were conducted with the port, captain, nausea, fishermen and boat management. The interview refers to the SOP of Freshwater Sales at PPN Sibolga. Interview results are weighted using the Guttman and Likert scale.Keywords: Freshwater, SOP Implementation, Service Quality, Freshwater Sales SOP.